Employment effects of investment grants and firm heterogeneity: Evidence from a staggered adoption approach - Eva Dettmann; Mirko Titze; Antje Weyh (Halle Institute for Economic Research (IWH), 2024)
This study estimates the firm-level employment effects of investment grants in Germany. In addition to the average treatment effect on the treated, we examine discrimination in the funding rules as potential source of effect heterogeneity. We combine a staggered difference-in-differences approach that explicitly models variations in treatment timing with a matching procedure at the cohort level. The findings reveal a positive effect of investment grants on employment development in the full sample. The subsample analysis yields strong evidence for heterogeneous effects based on firm characteristics and the economic environment. This can help to improve the future design of the program.
Keywords: A11; D61; H20; Z0; 330; causal inference; heterogeneous effects; place-based policy; staggered difference-in-differences; variation in treatment timing